Marine natural products2. Issue 3 (3rd February 2016) - Blunt, John W.; Copp, Brent R.; Keyzers, Robert A.; Munro, Murray H. G.; Prinsep, Michèle R.
Abstract : This review of marine natural products for 2014 describes 1378 new compounds and reports structural revisions or assignments of absolute configuration for previously reported compounds. Since 1965 MNP chemists have made ∼9000 collections worldwide yielding ∼25 700 new MNPs. The rate of discovery of MNPs by region is examined in this review. Abstract : Covering: 2014. Previous review: Nat. Prod. Rep., 2015, 32, 116–211 This review covers the literature published in 2014 for marine natural products (MNPs), with 1116 citations (753 for the period January to December 2014) referring to compounds isolated from marine microorganisms and phytoplankton, green, brown and red algae, sponges, cnidarians, bryozoans, molluscs, tunicates, echinoderms, mangroves and other intertidal plants and microorganisms. The emphasis is on new compounds (1378 in 456 papers for 2014), together with the relevant biological activities, source organisms and country of origin. Reviews, biosynthetic studies, first syntheses, and syntheses that lead to the revision of structures or stereochemistries, have been included.